2024
DOI: 10.1001/jamanetworkopen.2023.52302
|View full text |Cite
|
Sign up to set email alerts
|

Immune-Related Adverse Events and Survival Among Patients With Metastatic NSCLC Treated With Immune Checkpoint Inhibitors

Sarah Cook,
Vanessa Samuel,
Daniel E. Meyers
et al.

Abstract: ImportanceImmune-related adverse events (irAEs) secondary to immune checkpoint inhibitor (ICI) therapy reportedly improve overall survival (OS) in patients with non–small cell lung cancer (NSCLC). However, studies have been small and the association between irAE severity and OS remains poorly defined.ObjectiveTo examine the association between irAEs and their severity with OS in patients with locally advanced or metastatic NSCLC receiving ICIs.Design, Setting, and ParticipantsThis retrospective observational c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 68 publications
0
9
0
Order By: Relevance
“…Since irAEs re ect immune activation by ICI administration and are associated with therapeutic e cacy, we analyzed their association with the pre-and on-treatment biomarkers identi ed in the present study [13,14]. Our analysis revealed that pre-treatment biomarkers were not associated with development of irAE, whereas posttreatment changes in CCL23 were associated with the development of irAE.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Since irAEs re ect immune activation by ICI administration and are associated with therapeutic e cacy, we analyzed their association with the pre-and on-treatment biomarkers identi ed in the present study [13,14]. Our analysis revealed that pre-treatment biomarkers were not associated with development of irAE, whereas posttreatment changes in CCL23 were associated with the development of irAE.…”
Section: Discussionmentioning
confidence: 85%
“…We also analyzed the association and correlation between possible predictors of the therapeutic e cacy of ICI monotherapy and pre-and on-treatment biomarkers. Based on previous reports, irAE development, PD-L1 expression, CD8 + TIL density, peripheral blood cell count and proportion, and NLR were selected for examination [1][2][3][13][14][15][16][17].…”
Section: Selection Of Other Possible Predictorsmentioning
confidence: 99%
“…A growing body of evidence suggests that development of irAEs is associated with improvements in progression-free survival, overall survival and overall disease response rate (10)(11)(12)(13). Studies have demonstrated shared T cell receptor sequences and/or upregulated organ-specific transcripts between tumors and non-malignant tissues affected by irAEs, which suggest that irAEs and the anti-tumor immune response to ICIs could be mechanistically linked (14).…”
Section: Introductionmentioning
confidence: 99%
“…It is also important to note, that immunotherapy in the form of existing ICIs, is not quite as benign as was initially hoped. Significant levels of immunotherapy-related adverse events (irAEs) have been reported in non-small cell lung cancer (NSCLC) ( 68 , 69 ), melanoma ( 70 ) and HNSCC ( 71 ) especially when multiple ICIs are combined. Particularly problematic is the consistent observation that ICI toxicity and effectiveness are extremely correlated suggesting a substantial hurdle to ICI deployment for HNSCC particularly when combined with other toxic regimens/treatments.…”
Section: Introductionmentioning
confidence: 99%